The Eurozone: Similitudes and differences with Keynes's plan - Marc Lavoie (Hans-Böckler-Stiftung, Institut für Makroökonomie und Konjunkturforschung (IMK), 2015)
The eurozone is often considered to be the brainchild of Robert Mundell, who has often bragged about his paternity. In reality, the Eurozone setup, most specifically the TARGET2 settlement system, has several characteristics that look alike the plan for an international currency union that Keynes proposed in the early 1940s. The main objective of the paper is to show the similitudes and the differences between the Eurozone currency union and Keynes' Plan. The paper will also discuss some of the confusions that have arisen from the analysis of the TARGET2 system and the decision of the German constitutional court; and it will deal with the question of whether or not the European financial crisis of the GIIPS countries was akin to a balance-of-payments crisis as argued by some authors and denied by others. – – Die Eurozone wird häufig als geistiges Kind Robert Mundells betrachtet. In Wirklichkeit hat das Eurosystem, vor allem das TARGET2 Zahlungssystem, mehrere Eigenschaften, die Keynes Plan einer internationalen Währungsunion aus den 1940ern ähneln. Das Ziel dieses Beitrags ist die Ähnlichkeiten und Differenzen zwischen der europäischen Währungsunion und dem Keynes-Plan vorzustellen. Ebenso wird die aus der Analyse des TARGET2-Systems und dem Urteil des Bundesverfassungsgerichts entstandene Verwirrung diskutiert; und weiterhin wird die Frage behandelt, ob es sich bei der europäischen Finanzkrise um eine Krise der Zahlungsbilanzen handelt, wie von einigen Autoren argumentiert wird.
urn:nbn:de:101:1-2015032510721
Keywords: 330; Währungsunion; Europäisches Währungssystem; Zahlungsbilanz; Eurozone